Steroid‐dependent switch of OvoL/Shavenbaby controls self‐renewal versus differentiation of intestinal stem cells - Al Hayek, Sandy; Alsawadi, Ahmad; Kambris, Zakaria; Boquete, Jean‐Philippe; Bohère, Jérôme; Immarigeon, Clément; Ronsin, Brice; Plaza, Serge; Lemaitre, Bruno; Payre, François; Osman, Dani (The EMBO journal, 2021)
Adult stem cells must continuously fine‐tune their behavior to regenerate damaged organs and avoid tumors. While several signaling pathways are well known to regulate somatic stem cells, the underlying mechanisms remain largely unexplored. Here, we demonstrate a cell‐intrinsic role for the OvoL family transcription factor, Shavenbaby (Svb), in balancing self‐renewal and differentiation of Drosophila intestinal stem cells. We find that svb is a downstream target of Wnt and EGFR pathways, mediating their activity for stem cell survival and proliferation. This requires post‐translational processing of Svb into a transcriptional activator, whose upregulation induces tumor‐like stem cell hyperproliferation. In contrast, the unprocessed form of Svb acts as a repressor that imposes differentiation into enterocytes, and suppresses tumors induced by altered signaling. We show that the switch between Svb repressor and activator is triggered in response to systemic steroid hormone, which is produced by ovaries. Therefore, the Svb axis allows intrinsic integration of local signaling cues and inter‐organ communication to adjust stem cell proliferation versus differentiation, suggesting a broad role of OvoL/Svb in adult and cancer stem cells. SYNOPSIS How somatic stem cells integrate cell‐intrinsic and extrinsic cues to fine‐tune their output remains unclear. Here, the OvoL‐family transcription factor Shavenbaby (Svb) is shown to balance Drosophila intestinal stem cell (ISCs) fate decisions in response to systemic hormones. Svb is a direct target of EGFR and Wnt signaling in ISCs. Svb is switched from transcriptional repressor into activator by limited proteasomal degradation. Repressor Svb induces differentiation into enterocytes. Activator Svb promotes survival and proliferation of stem cells. The Svb repressor‐to‐activator switch is remotely induced by ovarian steroids. Graphical Abstract Post‐translational processing of the transcription factor Shavenbaby defines its dichotomous function in fly midgut homeostasis.